Health interests and needs in relation to healthful school living of elementary school pupils in the division of Occidental Mindoro and their implications to health education - Bautista, Aquilino P. 1913- (s.n.], 1968)
This is a survey of the health interests and needs of the elementary school pupils of Occidental Mindoro. It was conducted in an attempt to help improve the activities in school health education